How to interpret viral markers in the management of chronic hepatitis B infection. (March 2022) - Riveiro-Barciela, Mar; Pericàs, Juan M.; Buti, Maria
Abstract: Background: Hepatitis B virus (HBV) infection is a global public health issue with several unsolved clinical challenges. As multiple new drugs are under development, HBV markers are gaining importance for both diagnostic and prognostic purposes. Objectives: This review summarizes the most important data on the usefulness of HBV markers in the natural history of this infection, and in predicting clinical and treatment outcomes. Sources: Selected peer-reviewed publications on HBV markers published between January 2009 and July 2021. Content: In addition to the classical markers (e.g. HBV-DNA), newer ones, such as quantitative HBsAg, HBcrAg, HBV-RNA and quantitative anti-HBc, have proven useful for predicting events within the natural history of HBV infection, the development of complications (e.g. hepatocellular carcinoma) and the response to antiviral therapy. Most data regarding the response to treatment have been related to nucleos(t)ide analogues, whereas evidence on new therapeutic agents, such as capsid assembly modulators or small interference RNAs, is promising, but still scarce. Implications: Knowledge on the use of viral markers is a key factor for optimizing the clinical appraisal of HBV infection. The new markers have an enhanced ability to predict clinical outcomes. Further studies should expand the current evidence on the use of markers in relation to antiviral agents currently under evaluation. Wide availability of these markers in regions with a high incidence of HBV infection is of paramount importance.